Copper and Zinc in Three Dominant Brackish Water Fish Species from Paka Estuary, Terengganu, Malaysia - B.Y, Kamaruzzaman; K, Zaleha; M.C, Ong; K.Y.S, Wilson (Malaysian Journal of Science, 2007)
The concentrations of Cu and Zn in liver, stomach and gill tissues of three dominant edible fish species (Arius caelatus, Notopterus notopterus and Toxeres jaculatus)caught in Paka estuary were studied. A marked relationship between metal contents of the species studied was observed. The highest accumulation of the metals studied was found in liver samples, followed by stomach samples and lowest in the gill samples. In all cases, metal levels found were lower than the international standards of reference and the fish examined were not associated with enhanced metal content in their tissues and were safe within the limits for human consumption.